(untitled) (Linguostylistic Studies, 2016)
The article reveals peculiar features of the morphological expression of metaphor in Lina Kostenko’s collection "Garden of Not Melting Sculptures", which is recognized to be one of the defining characteristic features of the individual style of the poetess. The article highlights the essence/nature and classification of the metaphors revealed in the book. The metaphors are systematized according to their morphological parameters (verbal, nominal, adjectival). The article reports on the results of the analysis of morphological characteristics of metaphors and describes the features of their functioning. The emphasis is laid on those morphological parameters which allow the author to achieve the maximum aesthetic effect. The study seeks to find out the expressive means by which the metaphorical image is emphasized and how this affects the overall perception of the verse. The key findings of the research clearly demonstrate that using metaphor as a stylistic device of creating new poetic reality Lina Kostenko resorts to multilevel metaphorization represented by extended metaphors, achieving hereby the depth and multidimensionality of the poetic images. Key words: metaphor, metaphorization, tropes, figurative meaning, individual style. References